Analisis Perpindahan Kalor Pada Double Pipe Heat Exchanger Beraliran Lawan Arah Menggunakan Sirip Trapesium Dengan Fluida Cair - Muhammad Tsany Zulfahmi; Danar Susilo Wijayanto; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
This study aims to analyze the counter flow performance of a double pipe heat exchanger using an experimental method with the influence of the flow rate of hot and cold substances. The results showed that the counter-flow double-pipe heat exchanger produced a total heat transfer coefficient of 69.229 W/m2℃. The double pipe heat exchanger produces Reynolds number of 82.17 and Nusselt number of 1.18 in hot fluids, while in cold fluids it produces Reynolds number of 4.528.42 and Nusselt number of 31.52. The double pipe heat exchanger has an effectiveness rate of 116.16%.